Strategies for gravestone recording - Dunk, J; Rahtz, S (Manchester University Press, 1989)
This paper aims to show what we consider to be an ideal structure of database systems for the storage and manipulation of cemetery data, and how we arrived at this ideal. Examples quoted will, unless otherwise stated, be from the Protestant Cemetery in Rome, which was recorded on computer between 1984 and 1986, although the methodology can be applied to any graveyard or cemetery.